Characterization of Zygotic and Nucellar Embryo of Six Indonesian Mango Cultivars Using Molecular Markers - Fatimah, Fatimah; Husni, Ali; Kosmiatin, Mia; Karsinah, Karsinah; Baroya, Mushlihatun (Annales Bogorienses, 2016)
One of difficulties in mangoes hybridization is polyembryonic seeds. This phenomenon reduces the chance of recovering true hybrid seedlings. The identification of the zygotic embryo is difficult and the possible approach is by using molecular marker. The objective of this study was to evaluate the utilization of two different marker systems (dominant markers and SSR) to characterize the occurrence of zygotic or nucellar embryo in polyembryony mango cultivars Garifta Merah, Lalijiwo, Manalagi, Madu, Saigon Kuning, and Saigon Merah. The type of embryo was evaluated by comparing the exhibiting amplification patterns, if different from the mother plant considered as zygotic and identified as nucellar if they exhibited the same banding pattern as the mother plant. From both of this marker systems out of the 16 SSR and 16 evaluated dominant primers, nine primers of each systems amplified the largest number of allele and sharply defined band. Dendogram analysis showed that the evaluated dominant markers could distinguish the zygotic and nucellar embryo clearly compare to evaluated SSR primers. The number of zygotic embryos derived from SSR was 64% and dominant markers were 47%. Based on zygotic and nucellar size, number and position, indicating no relationship between the type of embryo and embryo size, number and the position.